2023
DOI: 10.3389/fendo.2023.1120127
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and BDNF levels in prediabetes and diabetes: A mediation analysis of a cross-sectional study

Abstract: AimClinical and epidemiological studies suggest links between dementias and Type 2 diabetes (T2DM). The underlying mechanisms of diabetes-related cognitive impairment are largely unknown. This study aims to investigate the role of BDNF in cognitive impairment in prediabetes and T2DM.MethodsThe study included 68 patients with prediabetes (preDM), 96 patients with T2DM, and 65 healthy controls. The cognitive function of the patients was evaluated with the Montreal Cognitive Assessment (MoCA) test and serum BDNF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Accumulating evidence supports the role of certain myokines in CVD, with some having the potential to serve as novel biomarkers reflecting disease development (Table 1 , Ref. [ 12 , 13 , 14 , 18 , 19 , 20 , 21 , 24 , 25 , 26 , 34 , 38 , 39 , 40 , 41 , 44 , 46 , 47 , 54 , 56 , 57 , 60 , 62 , 63 , 65 , 66 , 67 , 72 , 73 , 77 , 78 , 81 , 82 , 83 , 87 , 88 , 89 , 90 , 91 , 95 , 96 , 97 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 113 , 115 , 116 , 117 , 119 , 120 , 121 , 122 , 125 , 126 , 128 ]). Myokines are involved in CVD development and can provide new insights into CVD progression and help identify patients at a high risk of poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence supports the role of certain myokines in CVD, with some having the potential to serve as novel biomarkers reflecting disease development (Table 1 , Ref. [ 12 , 13 , 14 , 18 , 19 , 20 , 21 , 24 , 25 , 26 , 34 , 38 , 39 , 40 , 41 , 44 , 46 , 47 , 54 , 56 , 57 , 60 , 62 , 63 , 65 , 66 , 67 , 72 , 73 , 77 , 78 , 81 , 82 , 83 , 87 , 88 , 89 , 90 , 91 , 95 , 96 , 97 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 113 , 115 , 116 , 117 , 119 , 120 , 121 , 122 , 125 , 126 , 128 ]). Myokines are involved in CVD development and can provide new insights into CVD progression and help identify patients at a high risk of poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…BDNF plays a crucial role in pre-diabetes and T2DM cognitive impairment, where serum levels are considerably increased in T2DM patients. BDNF, therefore, could be a biomarker affected by T2DM and cognition [ 65 ]. The association between miR-1-3p expression and BDNF levels has been investigated in patients with essential hypertension.…”
Section: Brain-derived Neurotrophic Factormentioning
confidence: 99%
“…A protein called BDNF is essential for the development, upkeep, and plasticity of brain neurons [247]. Changes in BDNF levels in prediabetes patients may impact cognitive function [248]. A higher risk of neurodegenerative diseases and cognitive decline has been linked to decreased BDNF levels [249].…”
Section: Leptinmentioning
confidence: 99%
“…Its effects are mediated by the activation of tropomyosin receptor kinase B (TrkB), a member of the family of tyrosine kinase receptors [159]. Most of the studies have found reduced BDNF levels, both in diabetic animals and human patients, in a correlation with the intensity of memory decline, suggesting the important contribution of BDNF in the pathophysiology of cognitive impairment [97,[160][161][162][163][164][165]. Furthermore, the prevalence of depression is higher in diabetic patients, with a more prominent decrease in serum BDNF levels [166].…”
Section: Other Factors Contributing To Cognitive Dysfunction In Diabe...mentioning
confidence: 99%